Accumulation of mutations over the complete mitochondrial genome in tobacco-related oral cancer from northeast India. (August 2013) - Mondal, Rosy; Ghosh, Sankar Kumar
<x xml:space="preserve">Abstract</x> Northeast India has one of the world's highest incidences of oral cancer and 90% of them are related to tobacco. We examined the complete mitochondrial genome to determine hot spot mutations in oral cancer. The complete mitochondrial genome was sequenced using PGM™ from 10 patients matched blood and tumour tissue. Overall, 26 somatic mutations were found of which nine mutations in d-loop and 17 mutations in the coding region. The mutations at nucleotide positions 16294, 16325 and 16463 in d-loop and 4136, 13542 and 13869 in coding region are probably an indication to be a hot spot mutation in oral cancer. The knowledge about role, patterns and timing of mitochondrial mutations may serve to be facilitating clinical applications and hot spot mutations may be helpful in assessing cancer risk in tumour.